Feminist Analysis of Organizations: A Theoretical Perspective - Yasmin, Shakila (AIUB Journal of Business and Economics, 2015)
Organizational studies and feminist theories have long been detached due to their distinctive interest areas. Feminist scholars, only in the late 1960s and early 1970s, have condemned traditional organizational research to ignore issues of gender in working life. However, researches till date reveal that the gendered norms of ‘ideal workers’, the gendered division of labor are still prevalent and gender inequality has been institutionalized in organizations. Therefore, it’s legitimate to evaluate theories of organization from feminist perspective, such that an alternative gender neutral model of organization can be conceived. The objective of this paper is to identify existing theories about gender inequality in organizations. Based on secondary literature, seven major feminist approaches to organizations have been evaluated in terms of their argument and prescriptions for achieving gender equality. Liberal and psychoanalytic feminist approaches are transformative and mild, compared to others. Marxists frame gender difference as synonym to class struggle. Socialists on the contrary argue that a dual interlinked system of women’s oppression (capitalism and patriarchy) exist. Radicalists theorize sex to be the core of all sorts of oppression. They challenge all sex-based structures and take a separatist move. By examining multiple marginality and subordination of the third world women, post-modern and post-colonial feminists argue that previous feminists were focused only on the privileged women of developed economies. In terms of organizational practices, post-moderns and post-colonials prescribe a contingency approach, as such to take into account hybridity of identities.